2009
DOI: 10.1248/cpb.57.685
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Nematicidal and Antimicrobial Properties of Bis-[4-methoxy-3-[3-(4-fluorophenyl)-6-(4-methylphenyl)-2(aryl)-tetrahydro-2<i>H</i>-pyrazolo[3,4-<i>d</i>]thiazol-5-yl]phenyl]methanes

Abstract: A new series of bis-[4-methoxy-3-[3-(4-fluorophenyl)-6-(4-methylphenyl)-2-(aryl)-3,3a,5,6-tetrahydro-2H-pyrazolo[3,4-d][1,3]thiazol-5-yl]phenyl]methanes 6a-r was synthesized by the reaction of arylidine derivative of methylene-bis-thiazolidinones 5a-c with aryl/alkyl hydrazines. Chemical structures of all the new compounds were established by IR, (1)H-NMR, (13)C-NMR, MS and elemental data. The compounds 6a-r were evaluated for their nematicidal activity against Ditylenchus myceliophagus and Caenorhabdites eleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…7) However, to date there has been no phytochemical investigation into a related plant, A. quinquegona. From the n-hexane-and EtOAc-soluble fractions of the leaves of A. quinquegona, eight alkylated benzoquinones, named ardisiaquinones A-H (1)(2)(3)(4)(5)(6)(7)(8) were isolated along with four known compounds (9)(10)(11)(12) (Fig. 1).…”
mentioning
confidence: 99%
“…7) However, to date there has been no phytochemical investigation into a related plant, A. quinquegona. From the n-hexane-and EtOAc-soluble fractions of the leaves of A. quinquegona, eight alkylated benzoquinones, named ardisiaquinones A-H (1)(2)(3)(4)(5)(6)(7)(8) were isolated along with four known compounds (9)(10)(11)(12) (Fig. 1).…”
mentioning
confidence: 99%
“…Following the successful introduction of antimicrobial and nematicidal agents, inspired by the biological profile of triazoles, thiazolidenones, and in the continuation of our work on biologically active heterocycles, [27][28][29][30][31][32][33][34][35][36][37][38][39] we have developed a series of novel triazole linked thiazolidenone derivatives, and evaluated their nematicidal activity along with antibacterial activity.…”
Section: Srinivas Et Al: Synthesis and Biological Evaluation mentioning
confidence: 99%
“…23) In addition, it has been reported that thiadiazoles exhibit a broad spectrum of biological effectiveness such as anti-parkinsonism, 24) hypoglycaemic, 25) anticancer, 26) anti-inflammatory, 27) anti-asthmatic 28) and anti-hypertensive 29) activities. Inspired by the biological profile of pyrazole, triazole, thiadiazole, and in continuation of our research on biologically active heterocycles, [30][31][32][33][34][35] it was thought worthwhile to synthesize some new heterocyclic compounds containing pyrazole, triazole and thiadiazol rings in one molecular frame work. We report herein the synthesis of a new series of 1,2,4-triazole [3,4-b] [1,3,4]thiadiazoles bearing pyrazole and their antimicrobial activity.…”
Section: -7)mentioning
confidence: 99%